Loss of vitamin D receptor induces premature ovarian insufficiency through compromising the 7-dehydrocholesterol-dependent anti-aging effects - Chen, Haiyun; Wang, Qiuyi; Zhang, Yi; Shangguan, Luxi; Zhu, Zhengquan; Zhang, Huan; Zou, Xiang; Geng, Qinghe; Wen, Yanting; Wang, Daojuan; Wang, Yong (Frontiers in Cell and Developmental Biology, 2025)
Vitamin D has the potential to therapeutically affect the endocrine parameters of premature ovarian insufficiency (POI) patients. Previous research has indicated that serum vitamin D levels tend to decline with age and in individuals with POI. However, the precise impact of vitamin D deficiency on female fertility, especially their ovarian function, remains unclear. Vitamin D receptor (VDR) deficiency mice provide a model to investigate the possible effect of vitamin D on female reproduction. In this study, we observed abnormal follicular development in the Vdr deficiency mice. This anomaly is associated with reduced expression of anti-Mullerian hormone (AMH) and disrupted aromatase expression that disrupts the hormone secretion. Moreover, our findings indicate that Vdr deficiency disturbs redox balance, resulting in oxidative stress in the ovary, which further suppresses granulosa cell function and accelerates ovarian aging. Mechanistically, loss of Vdr inhibits de novo cholesterol synthesis by transcriptional repression of Hmgcr, and the antioxidant and anti-aging effects of the intermediate product 7-dehydrocholesterol (7-DHC) are also decreased. Treatment with 7-DHC effectively reduces ROS levels and alleviates aging in KGN cells deficient in Vdr. In conclusion, our results show that Vdr deficiency impairs follicle maturation and hormone secretion by accelerating granulosa cell aging, as a result of the reduced antioxidant and anti-aging effect of 7-DHC.